Penggunaan STEM (Science, Technology, Engineering, and Mathematics) Terintegrasi Pembelajaran berbasis Proyek untuk Mahasiswa - Pratama, Anggi Tias; Limiansi, Kintan; Anazifa, Rizqa Devi (INSTITUT AGAMA ISLAM NEGERI AMBON, 2020)
This study provides insights into STEM practices that are integrated with project-based learning. We show that when investigations into student interest and active participation, there are opportunities to experience project-based learning. The sample in the study was 30 students of biology education who attended environmental science lectures. The data analysis was carried out qualitatively with descriptive analysis to see the dominance of learning arrangements, learning activities, and the products of each of these learning settings. Students work on projects using the STEM learning steps. The results show that students can work on projects well, and are able to publish their work on YouTube. Keywords: STEM, Project-Based Learning, Environmental Science